2023
DOI: 10.3847/psj/acc253
|View full text |Cite
|
Sign up to set email alerts
|

Saturn's Seismic Rotation Revisited

Abstract: Normal mode seismology is a promising means of measuring rotation in gas giant interiors, and ring seismology presents a singular opportunity to do so at Saturn. We calculate Saturn’s normal modes of oscillation and zonal gravity field, using nonperturbative methods for normal modes in the rigidly rotating approximation, and perturbative methods for the shifts that Saturn’s deep winds induce in the mode frequencies and zonal gravity harmonics. The latter are calculated by solving the thermogravitational wind e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
3
0
0
Order By: Relevance
“…Note that the wind profile of Saturn is shown according to the latest estimate for the rotation rate (Mankovich et al, 2023). This estimate aligns with findings from the past two decades, indicating Saturn's rotation period to be approximately between 10 hr 32 min and 10 hr 34 min (Anderson & Schubert, 2007;Helled et al, 2015;Mankovich et al, 2019Mankovich et al, , 2023Read et al, 2009). Closer to the tangent cylinder there are strong retrograde flows reaching ∼30 m s 1 on Jupiter (Tollefson et al, 2017) and ∼90 m s 1 on Saturn (Garcia-Melendo et al, 2011) (Figures 1a and 1b).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Note that the wind profile of Saturn is shown according to the latest estimate for the rotation rate (Mankovich et al, 2023). This estimate aligns with findings from the past two decades, indicating Saturn's rotation period to be approximately between 10 hr 32 min and 10 hr 34 min (Anderson & Schubert, 2007;Helled et al, 2015;Mankovich et al, 2019Mankovich et al, , 2023Read et al, 2009). Closer to the tangent cylinder there are strong retrograde flows reaching ∼30 m s 1 on Jupiter (Tollefson et al, 2017) and ∼90 m s 1 on Saturn (Garcia-Melendo et al, 2011) (Figures 1a and 1b).…”
Section: Introductionsupporting
confidence: 83%
“…At the equatorial region, corresponding to outside from the tangent cylinder, both planets have a strong prograde flow (in the direction of rotation), which is superrotating within ∼6°(∼10°) latitude of the equator (Imamura et al, 2020) and reaching ∼100 m s 1 (∼300 m s 1 ) on Jupiter (Saturn) (Garcia-Melendo et al, 2011;Tollefson et al, 2017) (Figures 1a and 1b). Note that the wind profile of Saturn is shown according to the latest estimate for the rotation rate (Mankovich et al, 2023). This estimate aligns with findings from the past two decades, indicating Saturn's rotation period to be approximately between 10 hr 32 min and 10 hr 34 min (Anderson & Schubert, 2007;Helled et al, 2015;Mankovich et al, 2019Mankovich et al, , 2023Read et al, 2009).…”
Section: Introductionsupporting
confidence: 82%
“…The moments of inertia found in Wisdom et al (2022) used very different methods, but were found to be in remarkable agreement with one another. They are supported by more recent independent determinations (Mankovich et al 2023). The determination by Jacobson (2022) has larger estimated uncertainties, but is also compatible.…”
Section: Introductionsupporting
confidence: 74%